Antibody-ligand docking: Insights into peptide-carbohydrate mimicry - Yuriev, E.; Sandrin, M.; Ramsland, Paul (Taylor & Francis, 2008)
Despite the enormous clinical importance for xenotransplantation, very little is known about the 3D structural basis for natural antibody recognition of the major carbohydrate xenoantigen, its derivatives and their peptide counterparts. Fundamentally, understanding the nature of peptide-carbohydrate cross-reactivity is necessary to allow a rational design of useful inhibitors. To satisfy this need, we have initiated a project to investigate the structural aspects of antibody recognition of carbohydrate xenoantigens and their peptide mimics by molecular docking. We aim to analyse critical ligand-protein interactions with a focus on identifying the degree of structural carbohydrate mimicry exhibited by peptide ligands. In this paper, we present docking simulations of complexes between a prototypical xenoreactive monoclonal antibody and two ligands: the major carbohydrate xenoantigen, terminal galactose-(1,3)-galactose epitope [Gal(1,3)Gal] and a peptide inhibitor Galpep1 (DAHWESWL).